ln(a-10)-1=0

Simple and best practice solution for ln(a-10)-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(a-10)-1=0 equation:


Simplifying
ln(a + -10) + -1 = 0

Reorder the terms:
ln(-10 + a) + -1 = 0
(-10 * ln + a * ln) + -1 = 0

Reorder the terms:
(aln + -10ln) + -1 = 0
(aln + -10ln) + -1 = 0

Reorder the terms:
-1 + aln + -10ln = 0

Solving
-1 + aln + -10ln = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + aln + 1 + -10ln = 0 + 1

Reorder the terms:
-1 + 1 + aln + -10ln = 0 + 1

Combine like terms: -1 + 1 = 0
0 + aln + -10ln = 0 + 1
aln + -10ln = 0 + 1

Combine like terms: 0 + 1 = 1
aln + -10ln = 1

Add '10ln' to each side of the equation.
aln + -10ln + 10ln = 1 + 10ln

Combine like terms: -10ln + 10ln = 0
aln + 0 = 1 + 10ln
aln = 1 + 10ln

Divide each side by 'ln'.
a = l-1n-1 + 10

Simplifying
a = l-1n-1 + 10

Reorder the terms:
a = 10 + l-1n-1

See similar equations:

| 5x+10-x=10 | | 7-3x=6x-56 | | 4(4x+1)=4x-7x | | 13/3x-2=4/x | | x^4+5*x^3+9*x^2+8*x+4=0 | | 3-7x+2x=-37 | | 9x-26=30-5x | | 12t^2-5t+6=8 | | ln(p+10)=1 | | 8w+8=16 | | -9y+9=72 | | 0.30x+0.20(60)=0.15(32) | | -5(2x-9)=2(x-6)-11 | | 4x^4+8x^3+16x^2=0 | | 13x+3=29 | | 4w/3=4 | | 96x-624=336 | | -x+4x=8x-x+6 | | ln(6n)=3 | | (3x+3y)2= | | 5-2y=2+4y | | -5+x=-6x-5 | | f(x)=5-x^2/4 | | 0.36-a^2=0 | | 15=3r-3 | | 0.2047244=(1800*(96^3))/((10*10^6)*48*((b*(3.75^3)-(b-.5)*(3.25^3))/12)) | | 5.3x-6.45=7.95-4.3z | | g(-3)=0 | | -6x-3=5/7x-538/7 | | y=-3x+1.5 | | x+0.12x=1488 | | Log(x+1)16=8 |

Equations solver categories